In vitro screening of white Jute (Corchorus capsularis L) against salinity stress (Journal of Applied and Natural Science, 2015)
The environmental stress such as salinity of soil or water is serious threat for field crops in the world, especially in arid and semiarid regions. To study salinity stress on jute (Corchorus capsularis), an experiment was laid out in factorial randomized block design keeping nine capsularis varieties (JRC-698, JRC-321, JRC-517, JRC-7447, JBC-5, JRC-212, JRC-80, JRC-532 and UPC-94) as one factor and four levels of salt concentrations i.e. control (Distilled H2O), 100, 160, 240 and 300 mM NaCl with three replications. Adverse effect of salinity increased with increasing concentration of sodium chloride. Among nine jute varieties the highest germination percentage (89.5%), root length (0.6 cm), shoot length (1.2 cm), fresh weight (93 mg) and dry weight (9.5 mg) of seedling were observed in ‘JRC-698’ at salt concentration at 160 mM NaCl as compared with other salt concentration. All growth parameters were recorded higher in control than other treatments. All growth parameters were decreased up to 240 mM NaCl concentration and it was completely inhibited at 300 mM NaCl. Variety ‘UPC-94’ was the most susceptible to salinity stress. Hence, white jute varieties, JRC-698 and JRC-517 can be grown at 160 mM NaCl concentration.